Sex Workers' Self-Reported Physical and Mental Health in Greece: A Repeated Cross-Sectional Study in 2009, 2013 and 2019 - Nick Drydakis (Institute of Labor Economics (IZA), 2021)
In Greece, given the precarious nature of the sex work industry, sex workers health and wellbeing is of concern. However, relevant research remains limited. This study examined whether sex workers' self-reported physical and mental health deteriorated across time points during the economic recession in Athens, Greece. The study focused on 13 areas where off-street and street-based sex work occured. Cross-sectional data was collected from the same areas in 2009 (i.e. before the economic recession began) and in 2013 and 2019 (i.e. at time points during the recession). Self-reported physical and mental health decreased in 2013 and in 2019 compared to 2009. A positive association was found between the country's gross domestic product and sex workers' self-reported physical and mental health. The opposite was found for annual aggregate unemployment. The determinants of better self-reported physical and mental health were sex workers' economic condition, Greek nationality, off-street sex work, and registered sex work status. The opposite was found for more years' involvement in sex work and drug consumption. Findings indicate the need for more inclusive health strategies, especially during periods of economic downturn when sex workers' physical/mental health is likely to decline. This is the first study to investigate the association between economic recession and sex workers' self-reported physical and mental health.
Keywords: J81; G01; I10; I12; I18; 330; sex work; physical health; mental health; economic recession; drug consumption